Shotgun Metagenomic Sequencing Identifies Dysbiosis in Triplet Sibling with Gastrointestinal Symptoms and ASD - Sabine Hazan; Kimberly D. Spradling-Reeves; Andreas Papoutsis; Stephen J. Walker (MDPI AG, 2020)
The gut microbiome profile of a child with autism spectrum disorder (ASD) and co-occurring gastrointestinal (GI) symptoms was compared to that of her healthy triplet siblings to determine if she exhibited intestinal dysbiosis. Shotgun metagenomic sequencing was performed in individual fecal samples, and relative microbial abundance and diversity was determined. Microbial diversity was lower in sibling #3, coupled with a higher Bacteroidetes/Firmicutes ratio, a lower relative abundance of Actinobacteria, and an increased relative abundance of Proteobacteria. Our findings are suggestive of gut dysbiosis in a child with ASD and co-occurring GI symptoms, compared to her two healthy triplet siblings.